Aortic-brachial stiffness mismatch as potential marker of subclinical arterial damage in patients with rheumatoid arthritis - Elena A. Troitskaya; Sergei V. Velmakin; Lubov A. Goreva; Zhanna D. Kobalava (RUDN Journal of Medicine, 2023)
Aortic-brachial stiffness mismatch is a potential new marker of a subclinical vascular damage that has never been studied in patients with rheumatic diseases. The aim of the study was to assess the frequency of arterial stiffness mismatch in rheumatoid arthritis (RA) and to evaluate its clinical associations. Materials and Methods. The study group included 85 patients with RA (males 22.4 %, aged 59.7 ± 14.3 years, hypertension in 65 %, mean disease activity score (DAS-28 (C-reactive protein) 3.7 ± 1.1), and the control group included 40 subjects matched by gender, age and risk factors. The study methods included measurements of clinical and ambulatory brachial and aortic blood pressure (BP) (BPLab-Vasotens), arterial stiffness parameters parameters (applanation tonometry, SphygmoCorAtCor), cardio-ankle vascular index (VaSera) and cardio-vascular risk assessments using the SCORE, American College of Cardiology/American Heart Association (ACC/AHA) 2013 pooled cohort equations and QRisk2 scoring systems. The arterial stiffness gradient was calculated as a ratio between carotid-femoral (cf) and carotid-radial (cr) pulse wave velocity, and its elevation of ≥ 1 was considered as arterial stiffness mismatch. A p-value of 0.05 was considered significant. Results and Discussion. The mean stiffness gradient in RA patients without and with hypertension was 1.1 ± 0.1 and 1.4 ± 0.4, respectively (р 0.001); in controls, 0.99 ± 0.2 and 1.3 ± 0.3, respectively (р 0.001). The frequency of stiffness mismatch in the RA group was significantly higher compared to the controls in the whole study population (88.2 % vs 65 % (р = 0.002)) and in both normotensive and hypertensive subgroups (76.7 % vs 43.8 % (p = 0.03), and 94.5 % vs 79.2 % (p = 0.04), respectively). The same trend was observed in the subgroups with normal carotid-femoral pulse wave velocity: arterial stiffness mismatch was present in 82.1 % of RA patients vs. 51.9 % control subjects (p = 0.004). The stiffness gradient was associated with age (r = 0.63), hypertension duration (r = 0.56), cardio-vascular risk by the ACC/AHA 2013 (r = 0.69) and Qrisk2 (r = 0.7) scoring systems, nocturnal aortic systolic BP (r = 0.53), cardio-ankle vascular index (r = 0.60) and diurnal index of brachial systolic BP (r = -0.4). Significant differences in stiffness gradient values were observed in the subgroups based on elevation of aortic systolic BP and pulse wave velocity above individual reference values, aortic pulse pressure 50 mmHg, cardio-ankle vascular index 9, presence of high cardio-vascular risk, masked and nocturnal hypertension, and non-dipping. Conclusion. Patients with RA are characterized by higher frequency of arterial stiffness mismatch compared to controls, irrespective of the history of hypertension or the values of carotid-femoral pulse wave velocity. Arterial stiffness mismatch is associated with unfavorable 24-h BP profile, higher frequency of nocturnal hypertension and cardio-vascular risk.